Comparative Study of Non-Isolated and Isolated Bridge with TCFP Bearing Under Spatially Varying Ground Motions - YURDAKUL , Muhammet (International Journal of Computational and Experimental Science and Engineering, 2017)
In this study, stochastic behaviours of non-isolated and isolated highway bridges under spatially varying ground motion are examined. The triple concave friction pendulum (TCFP) bearing is used as a seismic isolation system which is easy to be manufactured and stand out against severe earthquake more than traditional seismic isolation systems. The spatially varying earthquake ground motion model includes wave-passage, incoherence and site-response effects. The incoherence effect is examined by considering the Harichandran and Vanmarcke coherency model. Soft and firm soil types are selected for considering the site-response effect where the bridge supports are constructed. The mean of maximum element forces and displacements of deck are examined in the study. Results from stochastic analysis of isolated and non-isolated bridges subjected to spatially varying ground motion are compared with each other for the special cases of the ground motion model. It is observed from stochastic analysis that the TCFP bearing decreases element forces of bridge deck by 61% to 93%. Also, it is pointed out that increasing of difference between the soils types at support points generally increase element forces and displacements.